Co-operative marketing for agricultural producers - Digby, Margaret; United Nations (Rome : Food and Agriculture Organization, 1955)
This book beginning with a brief exposition of marketing principles of general application, goes on to describe principles of co-operative marketing, how a co-operative is formed and financed, and what a marketing co-operative does.
Includes bibliographical references.
asm 24/01/2019
Loans
Keywords: Cooperative marketing; Cooperatives; Agriculture, Cooperative; Farm produce--Marketing